The Role of Empowering Santri Entrepreneurship in Pekalongan City - Dwi Aryani; Syarifatul ‘Amaliyah; a Mutiara Agus Virma; Arifatul Aini (MONETARIUM: Journal of Economics Business and Management, 2024)
The aim of this research is to analyze the role of empowering santri entrepreneurship in Pekalongan City. The research methodology used in this research is an intrinsic type of research, namely qualitative research that seeks to uncover meaning, investigate processes, and develop a comprehensive understanding and understanding of certain people, groups, or situations. The results of this research can be interpreted to mean that the supporting and inhibiting factors in economic empowerment are interrelated, but there are several ways to overcome them, namely by attending training both within the city and outside the city related to the fields involved in processing. Such as in the fields of marketing, management and production. Pekalongan City has a reputation as a religious, religious, trading and batik city. Apart from that, Pekalongan has been recognized as a creative city by UNESCO.